Local characterization of mobile charge carriers by two electrical AFM modes: multi-harmonic EFM versus sMIM. (7th February 2018) - Lei, Le; Xu, Rui; Ye, Shili; Wang, Xinsheng; Xu, Kunqi; Hussain, Sabir; Li, Yan Jun; Sugawara, Yasuhiro; Xie, Liming; Ji, Wei; Cheng, Zhihai
Abstract: The characterization of mobile charge carriers of semiconductor materials has spurred the development of numerous two dimensional carrier profiling tools. Here, we investigate the mobile charge carriers of several samples by multi-harmonic electrostatic force microscopy (MH-EFM) and scanning microwave impedance microscopy (sMIM). We present the basic principles and experiment setups of these two methods. And then several typical samples, i.e. a standard n-type doped Si sample, mechanical exfoliation and chemical vapor deposition grown molybdenum disulfide (MoS2 ) layers are systemically investigated by sMIM and MH-EFM. The difference and (dis)advantages of these two modes are discussed. Both modes can provide carrier concentration profiles and have sub-surface sensitivity. They also have advantages in sample preparation in which contact electrodes are not required and insulating or electrically isolated samples can readily be studied. The basic mode, physics quantities extracted, dielectric response form and parasitic charges in scanning environment result in difference in experiment results for these two kinds of methods. The techniques described in this study will effectively promote research on basic science and semiconductor applications.